Development of a reference material for water soluble chlorides (as NaCl) in feeding stuffs - Tagheen, Pochaman; Pondet, Sukanya; Romraluk, Srisuda (Bulletin of Applied Sciences, 2016)
This paper presented how to assign reference material value and measurement uncertainty for Water Soluble Chlorides (as NaCl) in Feeding Stuffs. This reference material was produced and its value was assigned from the proficiency testing round (PTCH-FA03-1401) organized by Center for Laboratory Proficiency Testing, Department of Science Service in accordance with ISO/IEC 17043, ISO Guide 34 and ISO Guide 35. The reference material is intended to be used for method validation, method verification and laboratory quality control. Target range for the reference material is set at 2.00 – 2.50 g/100g. The target measurement uncertainty for the reference material should not be more than 0.10 g/100g. The result show that the assigned value for the reference material is 2.292 g/100g and the measurement uncertainty is 0.064 g/100g at the 95% confidence level (k=2).